Application of Donabedian Quality-of-Care Framework to Assess the Outcomes of Medication Use in Pediatric ICU: A Review - Ali Mohammed Alhassan (International Journal of Scientific Research and Innovative Studies, 2024)
The Donabedian quality-of-care framework offers a structured approach to evaluating healthcare quality, encompassing structure, process, and outcome domains. Medication use in the pediatric intensive care unit (PICU) requires special attention due to the high-risk environment and vulnerable population. This review explores the application of the Donabedian framework in assessing medication use in the PICU, focusing on structural factors such as staffing and technology, processes such as prescribing and administration, and outcomes such as adverse drug events and clinical efficacy. Recommendations for improving quality and patient safety are discussed. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/274 https://doi.org/10.5281/zenodo.14480610